Hikers awarenesss on the trespassing impacts at Hutan Simpan Ayer Hitam - Jalaludin, Nurfazira (2019)
Hutan Simpan Ayer Hitam (HSAH) is a forest reserve that should be protected from any form of activities. However, the issue of trespassing for recreation activities had left a major impact on the forest environment such as trampling impact, pollution to the river, and wildlife disturbance (noise). The first objective of this study is to identify the awareness of the Wawasan trail hikers on trespassing impacts at HSAH. The second objective is to know the hikers’ understandings on the importance of HSAH as a forest reserve. The overall results indicated that hikers are well aware of the trespassing impacts at HSAH and do understand the importance of HSAH. The irony was the hikers’ years of hiking experiences not affecting their awareness of trespassing impacts. People are trespassing into HSAH because its location in the area of high-density population and it is a habit for the regulars to trespass although they are aware.